2018
DOI: 10.1039/c8cy01191e
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalate-based Gemini ionic catalysts for selective oxidation of benzyl alcohol with hydrogen peroxide in water

Abstract: Polyoxometalate-based Gemini ionic hybrids with inherent phase transfer capability are highly efficient and recyclable catalysts in the selective oxidation of alcohols with H2O2 in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…46,47 Noteworthy, the characteristic bands of hydroxyl groups (at 3450 cm . 48,49 It reveals the formation of Keggin-type ammonium PW in JNS-PW x . In particular, the WO d stretching vibration band shifts from 987 to 978 cm −1 , due to the ionic interaction in the PW-based hybrid.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…46,47 Noteworthy, the characteristic bands of hydroxyl groups (at 3450 cm . 48,49 It reveals the formation of Keggin-type ammonium PW in JNS-PW x . In particular, the WO d stretching vibration band shifts from 987 to 978 cm −1 , due to the ionic interaction in the PW-based hybrid.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…For benzyl alcohol oxidation L. Jing et al [127] We can also report a recent interesting work of Hao et al [128] They modified the phase increased with the length of the polyether chain (see Figure 14). The catalyst was tested for alcohol oxidation with hydrogen peroxide in 1.5 molar ratio.…”
Section:  Alcohols Oxidationmentioning
confidence: 55%
“…A remarkable enhancement of reaction rates with the employment of PIPA-13 was also observed in the case of 1-phenylethanol, cyclohexanol, diphenylmethanol, but for nhexanol or 2-phenylethanol the conversion is less than 17%. [128] with the permission from the Royal Society of Chemistry.) Qiao et al [105] reported two protic (N-dodecylimidazolium peroxotungstate 66% with a selectivity up to 99% (see Figure 15).…”
Section:  Alcohols Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] Nano carbon materials, e.g., carbon nanotubes (CNT), carbon spheres (CS), carbon bers (CF) and graphene, are becoming the most popular alternative supports due to their abundant earth-reserves and easily controlled surface chemistry. 20,21 Most important of all, strong synergy is hardly formed between gold and carbon (e.g., CNT) unless special treatment was processed. 22 The weak interaction between gold and CNT acts as a double-edged parameter.…”
Section: Introductionmentioning
confidence: 99%